ปัญหาและข้อจำกัดของพืชตัดแต่งพันธุกรรมในประเทศไทย - เทพชัย เทพช่วยสุข (มหาวิทยาลัยสงขลานครินทร์, 2024)
The aims of this study were to investigate the problems and limitations of GMOs crop in Thailand. This study concealed that the major problem of GMOs crop in Thailand was the consumers' and agriculturists' protection mechanism. The other problems were the biological safety of GMOs and international trade agreements. While the legitimate GMOs-regulatory organizations and genetic modification techniques were the minor problems and limilations. These conclusions were induced from the public hearing "Attitude of Thailand to GMOs" offered by The Department of Agricultural cooperation with Suekaset Company Limited on 27 September 1999 at Miracle Grand Hotel, Bangkok. Hence, an urgent corrective tendency of GMOs problems and limitations in Thailand was the establishment of protection mechanisms for consumers and agriculturists. Moreover, according to an evaluation of GMOs exports and any GMOs crop circumstances which occured in Thailand or in any foreign countries attributed to the further investigation of GMOs crop. Even though the GMOs crop in Thailand plight had been still obscure, this research contributed to the national solutions of GMOs so as to reinforce the utmost benefits to our country and our population.